Cassava agronomy research in China - Zhang, Weite; Lin, Xiong; Li, Kaimian; Juang, Jie; Tian, Yinong; Lee, Jun; Fu, Quohui (International Center for Tropical Agriculture, 1998)
Through cooperation with CIAT, national programs in China have paid more and more attention to cassava agronomy research and a lot of progress has been made. This paper describes briefly the most common cropping systems and production practices presently used by farmers. It also reviews the results of research on soil/crop management, with emphasis on soil fertility maintenance and soil erosion control, during the past decade.